Effects of Corni fructus on ovalbumin-induced airway inflammation and airway hyper-responsiveness in a mouse model of allergic asthma - Kim Seung-Hyung; Kim Bok-Kyu; Lee Young-Cheol (BMC, 2012)
Abstract Background Allergic asthma is a chronic inflammatory lung disease that is characterized by airway hyperresponsiveness (AHR) to allergens, airway oedema, increased mucus secretion, excess production of T helper-2 (Th2) cytokines, and eosinophil accumulation in the lungs. Corni fructus (CF) is a fruit of Cornus officinalis Sieb. Et. Zucc. (Cornaceae) and has been used in traditional Korean medicine as an anti-inflammatory, analgesic, and diuretic agent. To investigate the anti-asthmatic effects of CF and their underlying mechanism, we examined the influence of CF on the development of pulmonary eosinophilic inflammation and airway hyperresponsiveness in a mouse model of allergic asthma. Methods In this study, BALB/c mice were systemically sensitized to ovalbumin (OVA) by intraperitoneal (i.p.), intratracheal (i.t.) injections and intranasal (i.n.) inhalation of OVA. We investigated the effect of CF on airway hyperresponsiveness, pulmonary eosinophilic infiltration, various immune cell phenotypes, Th2 cytokine production, and OVA-specific immunoglobulin E (IgE) production. Results The CF-treated groups showed suppressed eosinophil infiltration, allergic airway inflammation, and AHR via reduced production of interleuin (IL) -5, IL-13, and OVA-specific IgE. Conclusions Our data suggest that the therapeutic effects of CF in asthma are mediated by reduced production of Th2 cytokines (IL-5), eotaxin, and OVA-specific IgE and reduced eosinophil infiltration.